Global Education in the Shadow of the Novel Coronavirus: Reflections on the Impact of COVID-19 Outbreak on Education Systems - Turgut Karakose (ÜNİVERSİTEPARK Limited, 2020)
This current issue of EDUPIJ includes two articles, each with different themes. In the first article, Ozkayran et al., evaluated guidance services, which play a crucial role in crisis management, based on the opinions of inservice teachers. In the second article, Stephens and McLaughlin examined the facilitating role of higher education in social media marketing.